Оцінка ефективності інвестиційних проектів з ліквідації вугледобувних підприємств, реалізованих на основі державно-приватного консорціуму - Сердюк, О.С. (Економіка промисловості, 2016)
Досліджено показники ефективності інвестиційних проектів, доведено доцільність використання показника чистої приведеної вартості (NPV) в умовах оцінки ефективності проектів ліквідації вугледобувних підприємств, виявлено особливості руху грошових потоків при реалізації проектів з демонтажу устаткування та ліквідації гірничих виробок, відповідно до виявлених властивостей удосконалено формулу розрахунку NPV. Исследованы показатели эффективности инвестиционных проектов, доказана целесообразность использования показателя чистой приведенной стоимости (NPV) в условиях оценки эффективности проектов ликвидации угледобывающих предприятий, выявлены особенности движения денежных потоков при реализации проектов по демонтажу оборудования и ликвидации горных выработок, в соответствии с выявленными свойствами усовершенствована формула расчета NPV. The indicators of efficiency of investment projects are investigated. The conclusion about feasibility of their use in evaluating the effectiveness of projects on liquidation of coal mines is made. The expediency of use of IRR, MIRR, DPP, PP and PO indicators as performance criteria for investment projects for liquidation of coal mines is analyzed. The assessment of the importance of profits discounting is provided. The features of realization of measures on liquidation of coal mines are identified. The expediency of use of the net present value (NPV) in conditions of efficiency estimation of projects for coal mines elimination is proved. The features of the cash flows in the implementation of the two main types of projects are given: dismantling of equipment and liquidation of underground tunnels; processing of mining dumps. The methodical recommendations on the calculation of cash flow in conditions of projects for coal mines liquidation are proposed. The formula for calculating net cash flows in terms of projects is given: dismantling of equipment and liquidation of underground tunnels; processing of mining dumps. The formula for calculating NPV based on accounting the features of movement of cash flows is improved. Net NPV for projects for dismantling of equipment and coal mines liquidation at the mines Pivdenna, Zarichna, Novovolynska №1 is calculated. The factors are given, based on which the decision on the formation of a model of public private consortium is made. The recommendations about formation of coal sector restructuring program are given. The directions of further research are determined.